2021
DOI: 10.1113/jp280970
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the mode of heating on cerebral blood flow, non‐invasive intracranial pressure and thermal tolerance in humans

Abstract: Key points The human brain is particularly vulnerable to heat stress; this manifests as impaired cognition, orthostatic tolerance, work capacity and eventually, brain death. The brain's limitation in the heat is often ascribed to inadequate cerebral blood flow (CBF), but elevated intracranial pressure is commonly observed in mammalian models of heat stroke and can on its own cause functional impairment. The CBF response to incremental heat strain was dependent on the mode of heating, decreasing by 30% when ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 81 publications
5
27
0
Order By: Relevance
“…These results by Gibbons and colleagues (2021) provide novel evidence that reductions in cerebrovascular CO 2 reactivity per se likely contribute favourably to CBF regulation during severe heat stress. Additionally, as reductions in CBF during severe heat strain did not dictate thermal tolerance or affect exercise performance, these results may indicate an increased possibility of cerebral oxidative/pro‐inflammatory stress (via reduced convective heat loss) with prolonged sauna/spa heat therapy and hyperthermic exercise prior to achieving subjective tolerance.…”
Section: Figure the Influence Of Cerebrovascular Sensitivity To Co2 On Cerebral Blood Flow (Cbf) During Severe Heat Strain To Thermal Tolmentioning
confidence: 72%
See 1 more Smart Citation
“…These results by Gibbons and colleagues (2021) provide novel evidence that reductions in cerebrovascular CO 2 reactivity per se likely contribute favourably to CBF regulation during severe heat stress. Additionally, as reductions in CBF during severe heat strain did not dictate thermal tolerance or affect exercise performance, these results may indicate an increased possibility of cerebral oxidative/pro‐inflammatory stress (via reduced convective heat loss) with prolonged sauna/spa heat therapy and hyperthermic exercise prior to achieving subjective tolerance.…”
Section: Figure the Influence Of Cerebrovascular Sensitivity To Co2 On Cerebral Blood Flow (Cbf) During Severe Heat Strain To Thermal Tolmentioning
confidence: 72%
“…5 C of Gibbons et al . 2021). These data are supported by classic work by Harper and Glass (1965) who showed that substantial hypotension effectively overrules the vasoconstrictive ability of the cerebrovasculature to respond to reductions in PnormalaCO2 (Harper & Glass, 1965).…”
Section: Figure the Influence Of Cerebrovascular Sensitivity To Co2 On Cerebral Blood Flow (Cbf) During Severe Heat Strain To Thermal Tolmentioning
confidence: 99%
“…It is well established that the brain, in particular the centres responsible for cardiorespiratory control, responds rapidly to homeostatic perturbations such as hypoxia (Bailey et al, 2009;Gibbons et al, 2020) and increases or decreases in temperature (Caldwell et al, 2020;Gibbons et al, 2020Gibbons et al, , 2021. In turn, the subsequent detrimental effects of hypoxia on cognitive performance have also been well-studied (see McMorris et al, 2017 andAndo et al, 2020 for a review).…”
Section: From Pigeon Holes To Descending Spirals: a Paradigm Of Physiology Cognitive Performance And Behaviour In Extreme Environmentsmentioning
confidence: 99%
“…This hyperventilation results in excessive elimination of CO 2 from the body, which leads to reductions in arterial CO 2 pressure (Pa CO 2 ) (hypocapnia) (5,(12)(13)(14)(15). Because Pa CO 2 is a key determinant of cerebral circulation (16)(17)(18)(19)(20), the hypocapnia likely contributes to the cerebral hypoperfusion, as indicated by a reduction in middle cerebral artery mean blood velocity (MCAV) during hyperthermia (5,6,(21)(22)(23)(24). This cerebral hypoperfusion may limit heat exchange within the brain (25,26) as well as the fuel supply for the brain's increasing metabolism during hyperthermia (13,27).…”
Section: Introductionmentioning
confidence: 99%
“…It seems plausible, therefore, that sodium bicarbonate ingestion could attenuate heat-induced hyperventilation during exercise in the heat and, in turn, the hypocapnia. If so, the reduction in hypocapnia associated with sodium bicarbonate ingestion may increase cerebral blood flow, as hypocapnia is the primary factor causing cerebral vasoconstriction during prolonged exercise in the heat (6,23). Up to now, however, these possibilities have not been directly tested.…”
Section: Introductionmentioning
confidence: 99%